2018
DOI: 10.1186/s40942-017-0104-9
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune retinopathy: A Review

Abstract: Autoimmune retinopathy (AIR) is a rare and still poorly understood immune-mediated disease that may cause inflammation from circulating autoantibodies against the retina. It may be related to history of autoimmune disease in the patient or in a family member or the presence of neoplastic disease in the individual. The disease may be subdivided into paraneoplastic and non-paraneoplastic AIR. When related to melanoma, it is referred to as MAR, and when related to other cancers, it is called CAR. The exact preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 21 publications
4
68
0
5
Order By: Relevance
“…In this study, we report three novel cases with MAR being in fact females. It has been suggested that MAR is more prevalent in male [8], due to melanoma being more prevalent in male patients, especially after 50 years [58,59]. However, our studied cases were all female patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, we report three novel cases with MAR being in fact females. It has been suggested that MAR is more prevalent in male [8], due to melanoma being more prevalent in male patients, especially after 50 years [58,59]. However, our studied cases were all female patients.…”
Section: Discussionmentioning
confidence: 69%
“…Paraneoplastic retinopathies are rare retinal disorders usually associated with the presence of autoantibodies against retinal proteins following the development of a primary tumor or a metastasis [1][2][3][4][5]. Two major types of paraneoplastic retinopathies with an initial normal fundus have been reported: (1) cancer-associated retinopathy (CAR), which leads to a rapid and severe visual dysfunction with primary photoreceptor alterations and is most commonly associated with small-cell carcinomas of the lung and less frequently associated with breast, endometrial and other cancers [6,7]; (2) melanoma-associated retinopathy (MAR), traditionally associated with metastatic melanoma [2] but now well recognized in association with other cancers such as carcinomas [8][9][10][11]. Patients presenting with MAR usually experience recent night blindness, photopsias (various perception of flickering lights), decreased vision and alterations of the visual field.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying malignancies should be ruled out before the diagnosis of npAIR is made. [3] Signs and symptoms may be diverse and overlapping, depending on the cell type and antigen targeted by ARAs. Patients usually present with acute or subacute, bilateral vision loss, visual field defects, nyctalopia, scotomas, and photopsia.…”
Section: Discussionmentioning
confidence: 99%
“…The management of npAIR is also controversial. There is no global consensus on the management or prognosis of AIRs [3] because most of our knowledge comes from case reports and case series. Suggested approaches include systemic and local corticosteroids, antimetabolites such as mycophenolate mofetil, azathioprine, and T cell inhibitors such as cyclosporine, targeted B-cell therapy such as anti-CD20 monoclonal antibody (rituximab), IVIG, and plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%
“…Mr Price-Hunt was also checked extensively for autoimmune retinopathy (AIR), which can sometimes present with diffuse retinal atrophy, macular oedema, and minimal findings on ophthalmic examination [8]. AIR is a type of immune-mediated disease caused by circulating autoantibodies against the retina, which can on occasion be due to the presence of neoplastic disease [9]. This was why he had investigations to rule out neoplastic disease, including fullbody computed tomography (CT) scans, positron emission tomography (PET) scans, a magnetic resonance imaging (MRI) brain scan with contrast and a cerebrospinal fluid examination to rule out infection and autoimmune and demyelinating diseases.…”
Section: Physicians' Responsementioning
confidence: 99%